Do Employee Share Owners Face Too Much Financial Risk? - Douglas L. Kruse; Joseph Blasi; Dan Weltmann; Saehee Kang; Jung Ook Kim; William Castellano (Institute of Labor Economics (IZA), 2019)
A major theoretical objection against employee ownership is that workers become inadequately diversified and exposed to excessive financial risk. Recent theory concludes that 10-15% of a worker's wealth portfolio can be prudently invested in employer stock provided the rest of the portfolio is properly diversified. This paper analyzes employee share ownership in U.S. family financial portfolios using data from the 2004-2016 Survey of Consumer Finances. We find that 15.3% of families with private-sector employees had employer stock in their portfolio, with a median value of 6,000 and a median percent of family net worth of 3.1%. About one in five (19.2%) of the families with employer stock exceed the 15% threshold. This may be overstated given that the 15% threshold pertains to purchased stock and not to stock granted with no sacrifice by the employee. A higher percentage of families exceed the threshold for stock bought directly than for stock in pension plans. The analysis shows that employee ownership appears to generally add to, rather than substitute for, other wealth, which lessens the financial risk. We also find that families with employer stock are found to express more tolerance of financial risk, have higher self-rated knowledge of personal finances, and are more likely to understand the value of diversification. While financial risk does not appear to represent a substantial problem in practice for most employee share owners, a small minority may face excessive risk. We conclude with approaches to address excessive financial risk in company stock when it appears.
Keywords: J32; J33; J54; D31; P13; 330; employee ownership; financial risk; wealth; diversification